Doors Closed and Opportunities Missed: Lessons from Failed Automotive Investment Attraction in Canada in the 1980s - Mordue, Greigory D. (Canadian Public Policy, 2017)
During the 1980s, Canada's automotive manufacturing assembly landscape changed when five new manufacturers from outside of North America made large-scale investments. The industry shifted from one focused on US-owned corporations to one with a much more international orientation. Because of the success Canada enjoyed in attracting foreign automotive investment, one might conclude that those engaged in the process did so with a coherent plan and that the period was marked by one success after another. The reality, however, is that several misses also occurred. Layering archival sources and interviews with secondary sources, this article contributes to the history of the economic development of Canada's automotive industry. Through this, important lessons for policy-makers are offered: The process of goal and policy congruence is demonstrated; one sees how dominant personalities can override governance mechanisms, even in large corporations; and one observes the capacity of exogenous factors to affect the best-laid plans.